INVESTIGATING THE RELATIONSHIP BETWEEN METACOGNITIVE STRATEGIES AND READING PROFICIENCY AMONG THE UNIVERSITY OF JEDDAH LEARNERS - Alqahtani, Saleh Mohammad Ali (Acta Scientiae et Intellectus, 2024)
There exist various factors that enhance the reading comprehension and thus a significant role is played by the metacognitive reading strategies in this enhancement. Some studies focus on claiming the relation among reading proficiency, reading motivation, and strategies of metacognitive reading. Furthermore, this study tries to focus on the awareness level as well as metacognitive reading strategies usage when students’ read texts related to academics in English, their motivation level as well as their interests and performance in reading by using the instrument of Survey of Reading Strategies (SORS) (Mokhtari & Richard, 2002) having subscales of global strategies, problem-solving and support strategies. The goal of this study was to fill this gap through a comparison of 197 (96 = male; 101 = female) academic reading strategies. The results indicate that students of the University of Jeddah appear to use challenging approaches more frequently than regional and promotion methods, which confirm their previous studies. Moreover, it also revealed that there was a momentous variation level in the strategies used by the female and male students. The association between the reading approaches adopted by the students to increase their reading proficiency was significant. The results proved that the participants had a good understanding and reasonable control of the metacognitive strategies while reading the academic texts.